2013
DOI: 10.1371/journal.pone.0078109
|View full text |Cite
|
Sign up to set email alerts
|

Correlational Analysis of neck/shoulder Pain and Low Back Pain with the Use of Digital Products, Physical Activity and Psychological Status among Adolescents in Shanghai

Abstract: PurposeThis study investigates the neck/shoulder pain (NSP) and low back pain (LBP) among current high school students in Shanghai and explores the relationship between these pains and their possible influences, including digital products, physical activity, and psychological status.MethodsAn anonymous self-assessment was administered to 3,600 students across 30 high schools in Shanghai. This questionnaire examined the prevalence of NSP and LBP and the level of physical activity as well as the use of mobile ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
199
3
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(231 citation statements)
references
References 36 publications
(47 reference statements)
19
199
3
10
Order By: Relevance
“…A total of 31% reported a new onset of LBP. The prevalence of LBP in the present study was the same as a recent study from China that also showed the prevalence of LBP among adolescents living in Shanghai, was 33.1% (Shan et al, 2013). One of the limitations in this study was that only adolescents from one school were included.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…A total of 31% reported a new onset of LBP. The prevalence of LBP in the present study was the same as a recent study from China that also showed the prevalence of LBP among adolescents living in Shanghai, was 33.1% (Shan et al, 2013). One of the limitations in this study was that only adolescents from one school were included.…”
Section: Discussionsupporting
confidence: 51%
“…A related study on low back pain among adolescents in Shanghai (Shan et al, 2013), reported a prevalence of 33.1%. The sample size calculated with infinite population was Therefore, the sample size (n) was 3,120 participants…”
Section: Sample Size Calculationmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, problematic smartphone use is related to traffic accidents (Cazzulino, Burke, Muller, Arbogast, & Upperman, 2014;Thompson, Rivara, Ayyagari, & Ebel, 2013), shoulder and neck problems (Shan et al, 2013;Xie, Szeto, Dai, & Madeleine, 2016), sleep impairment (Demirci, Akgonul, & Akpinar, 2015;Eyvazlou, Zarei, Rahimi, & Abazari, 2016), academic problems (Seo, Park, Kim, & Park, 2016), and poor physical fitness (Rebold, Sheehan, Dirlam, Maldonado, & O'Donnell, 2016). Furthermore, problematic smartphone use is related to mental health problems such as anxiety and depression (reviewed in .…”
Section: Introductionmentioning
confidence: 99%
“…This fact happens because, generally, regular physical activity in adolescence is more exercised by boys, through games, and competitive sports, which provides improvement in muscle strength/ endurance 25 . In addition, hormonal differences arising from the maturational process in the adolescence phase provide a better performance in physical tests by the boys compared to the girls 25,26 . Therefore, it is important to encourage, especially in females, the regular practice of physical activity in order to improve and possibly develop better levels of lumbar force.…”
Section: Resultsmentioning
confidence: 99%